Transformation des structures agricoles et recomposition des paysages de bocage - Thibaut Preux; Daniel Delahaye; Maxime Marie (Projets de Paysage)
In the region of Basse-Normandie, the process of “agricultural modernisation” started in the 1950s has led to an unprecedented reorganisation of rural spaces and landscapes. The irregularity of the fabric of land plots was corrected by successive land consolidation schemes the stated objective of which was to “do away with the past”. However, in spite of the significant reduction in the number of land consolidation schemes since the 1990s, the rationalisation of the bocage landscapes has been continued. In this article we propose a method for interpreting the transformation of the bocage landscapes, while attempting to provide a detailed description of the underlying mechanisms causing this transformation. A spatial analysis of the dynamics in the landscape was conducted and completed by a survey among farmers. In spite of public statements and actions in favour of maintaining and even restoring bocage landscapes, the results of this study suggest that the changes in the structure of farms (larger establishments, their concentration and the specialisation of production) has contributed to the erosion of these landscapes which are emblematic of these western rural areas and has led to the emergence of new forms of landscapes.